The dressmaker of Khair Khana : five sisters, one remarkable family, and the woman who risked everything to keep them safe - Tzemach Lemmon, Gayle. (Harper, 2011)
The incredible true account of Kamila Sidiqi who, when her father and brother were forced to flee Kabul, became the sole breadwinner for her five siblings. Armed only with grit and determination, she picked up a needle and thread and created a thriving business of her own and held her family together.